Lutas Sociais, vol. 25, n. 47, Jul./Dez. 2021 - Sociais, Lutas (Lutas Sociais, 2023)
Editor: Lúcio Flávio de Almeida (PUC, São Paulo-SP) Comitê editorial Eliel Machado (UEL, Londrina-PR), Ilse Gomes Silva (UFMA, São Luís-MA), Jair Pinheiro (UNESP, Marília-SP), Lúcio Flávio de Almeida (PUC, São Paulo-SP), Zulene Muniz Barbosa (UFMA, São Luís-MA).